ANALISA KERAGAMAN KARAKTER TANAMAN MANGGIS DI KABUPATEN POSO BERDASARKAN IDENTIFIKASI MORFOLOGI DAN ANATOMI - Ruslan Ruslan; Enny Adelina; Jeki Jeki (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
Mangosteen (GarciniamangostanaL.) is Indonesia's flagship fruit commodity which is widely distributed in Central Sulawesi with high export value and very potential to be developed into superior export commodities. Central Sulawesi has good mangosteen production potential, but it is still on the scale of house yard.  Thus, to increase the potential of mangosteen production, it is necessary to provide selected trees which can be used as seed sources. This research used survey and direct descriptive method, and data obtained was analyzed using cluster analysis. The research was conducted inPamona and Tendeadongi villages, Pamona Utara sub-district, Poso District. The analysis of mangosteen leaf anatomy was carried out in the Laboratory of Plant Pests and Diseases of Faculty of Agriculture, University of Tadulako. This study was conducted from December 2016 to February 2017. The results of cluster analysis showed that there are three different accession groups in either village.  The groups in Pamona village were PM4, PM7 and PM3 whereas in Tendeadongiwere TD15, TD1 and TD13. The combined accession between mangosteen of Pamona and Tendeadongivillage areconsisted of four different accessional groups represented by PM3, TD1, TD13 and TD15.Keywords: Anatomy,cluster, mangosteen, and morphology.